CAPACITY CALCULATION OF RIVER FOR PADDY FIELDS SECTIONAL KECAMATAN KOTA BANGUN KABUPATEN KUTAI KARTANEGARA - KUSASI, ACHMAD (KURVA S JURNAL MAHASISWA, 2014)
Cros section of the river and chanel capacity are inadequate oftenacused of being the main cause of floding , it is also suported by pormaintenance and management of the river system coupled with a lack of publicawarenes to dispose of waste in place.The river that is the source of life ,god water source, means of transportstreams, irigation facilties and irigation is often used as a landfil whichresulted in a cros- river narowed ,sedimentation and reduce capacites.By knowing the capacites of existing river cros-section, it may be anaproach to the management and maintenance efort of this river, so the negativeefects can be prevented, but he impact and the positve potential of this river canbe utilzed ,especialy in flod control eforts and as a source of water rice fieldsin the District City Build.Water discharge ocurs by repeated periods of 10, 20 and 50 years whichflows into the river city district build rice field area with a maximum value of16.818 m3/sec and sediment discharge of 1,597 m3/sec .